CAS 2010 Proceedings (International Semiconductor Conference) 2010
DOI: 10.1109/smicnd.2010.5650503
|View full text |Cite
|
Sign up to set email alerts
|

The advantages, limitations and disadvantages of Z-source inverter

Abstract: A Z-source converter is an unique x-shaped impedance network called Z-source impedance network that couples the converter main circuit to the power source. The converter may be of all conversion types -if it is of ac-to-dc type, the z-source converter is called z-source inverter. Since 2003 when this recently conversion concept appeared [1], it proved able to solve many conversion problems. In this paper it's superiority compared to traditional solutions are shown. There are also small disadvantages and limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Three different inverters were investigated in different applications and it is shown that 'Z-source' inverter is very promising in power converter applications. Florescu and other authors in [1] have highlighted the advantages, limitations and disadvantages of Z-source converter. Peng has presented several power converter configurations [7] that overcomes the limitations and problems of traditional power source converters.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Three different inverters were investigated in different applications and it is shown that 'Z-source' inverter is very promising in power converter applications. Florescu and other authors in [1] have highlighted the advantages, limitations and disadvantages of Z-source converter. Peng has presented several power converter configurations [7] that overcomes the limitations and problems of traditional power source converters.…”
Section: Literature Surveymentioning
confidence: 99%
“…The unique feature of the Z-source converter is that unlike the traditional converters it can be open and shortcircuited which provides a mechanism for main circuit to step-up or step-down the voltage as desired [1]. Hence the output voltage can be of any value between zero and infinity i.e the obtainable range of voltage is quiet wide.…”
Section: Working Of Z-source Convertermentioning
confidence: 99%
“…One of the characteristics of the buck inverter is that the instantaneous average output voltage is always lower than the input dc voltage [11][12][13][14][15][16][17]. Buck inverter is a dc-ac converter which can not produce an output voltage greater than the input voltage, but it is easy to be controled .This converter performs in a simplified way, turning on and off the switches to produce a bipolar square output voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The Z-source inverter has two capabilities such as, shoot-through duty cycle and modulation index. But the drawback of Z-source inverter is that the Z-source inverter has lower average switching device power in low boost ratio range [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristics of the buck inverter is that the instantaneous average output voltage is always lower that the input dc voltage [11][12][13][14][15][16][17]. Buck inverter is a dc-ac converter which can not produce an output voltage greater than the input voltage, but it is easy to be controled .This converter operates, in a simplified way, turning on and off the switches to produce a bipolar square output voltage.…”
Section: Introductionmentioning
confidence: 99%